The Efficacy of Application of Oral Antibiotic Loaded Polymethyl Methacrylate Against Staphylococcus aureus - Rahmadian, Rizki; Edison, Ebill Fuji; Kaharudin, Kaharudin; Irrahmah, Miftah; Putra, Andani Eka (Indonesian Journal of Multidisciplinary Science, 2023)
Chronic osteomyelitis is still common in the developing world and presents a continuing therapeutic challenge. Local antibiotic therapy is performed as the first stage treatment algorithm for 4 to 8 weeks. Given the high patient morbidity, mortality, and economic burden caused by osteomyelitis and its treatment, it is important to find another effective and efficient treatment.  Intravenous antibiotics and polymethylmethacrylate (PMMA) combination have shown effectiveness, but the potential of oral antibiotics and PMMA combination is still rare and is debatable. It aimed to compare efficacy among oral antibiotic-loaded PMMA in many concentrations (5%, 10%, 20%) and controls (0%) against Staphylococcus aureus. This experimental study was conducted in the Microbiology Department of Andalas University. The object was S. aureus. We used ten oral antibiotics and compared among its many concentrations (5%, 10%, 20%) and controls (0%).  Data were analyzed by analysis of variance (ANOVA) test. The lowest counts of S. aureus were found in ciprofloxacin 20%, followed by tetracycline 10%, erythromycin 5%, rifampicin 10%, ofloxacin 20%, clindamycin 20%, amoxiclav 20%, cefixime 5%, cotrimoxazole 20%, and chloramphenicol 20% consecutively. All oral antibiotics loaded PMMA in each concentration might reduce the number of colonies up to 90%. A study in 2013 revealed that a combination of several antibiotics and PMMA was proven to be effective. The oral antibiotics loaded PMMA in various concentrations have a significant bactericidal effect on the growth of S. aureus and able to reduce the number of S. aureus.